Operation control procedures of an air crew to operate an aircraft - Godunov, A.I.; Kuatov, B.Zh.; Sushchik, D.M. (Bulletin of the Karaganda University. Mathematics Series, 2015)
This paper considers operation control procedures of an air crew to operate an aircraft. Therefore, we envisage an aircraft control carried out by a human-operator. It’s noted, that such interaction has the piecewise continuous character and represents a complex of individual operations with the set of conditions defining its beginning and ending. The logical check of the aircraft movement control lies in conformance inspection of operators control logic actions in current time. The analysis of an air crew operator performance during the aircraft operation allowed to define the list of possible errors resulted in this activity.